2015
DOI: 10.17219/acem/23171
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and Delivery in Women with Uterine Malformations

Abstract: Background. Uterine defects are the most common malformations of the female reproductive system. They can lead to many obstetric complications, e.g. preterm delivery, intrauterine growth restriction, oligohydramnios and operational delivery. Objectives. Our aim was to analyze the impact of different types of uterine defects on pregnancy outcomes. Material and Methods. The study involved 94 pregnant women with different types of uterine defects hospitalized at the Department of Fetal -Maternal Medicine and Gyne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Bicornuate uterus is positioned between these two extremes and, being a unification defect, it derives from an abnormal fusion of the ducts. Literature data show that patients with a uterine anomaly have a poor pregnancy outcome, with a tendency to undergo abortion, preterm delivery, or operative birth [87,88]. The higher risk of rupture of anomalous uteri in the first trimester is still unexplained.…”
Section: First-trimester Uterine Rupture In Unscarred Uterusmentioning
confidence: 99%
“…Bicornuate uterus is positioned between these two extremes and, being a unification defect, it derives from an abnormal fusion of the ducts. Literature data show that patients with a uterine anomaly have a poor pregnancy outcome, with a tendency to undergo abortion, preterm delivery, or operative birth [87,88]. The higher risk of rupture of anomalous uteri in the first trimester is still unexplained.…”
Section: First-trimester Uterine Rupture In Unscarred Uterusmentioning
confidence: 99%
“…Consistent with published data, most patients required a cesarean delivery in our cohort, primarily for malpresentation. 6,[8][9][10][11]14,[22][23][24] Previous studies have reported on the increased risk for adverse pregnancy outcomes in women with abnormal uteri. Most of these studies include all congenital uterine anomalies collectively or a cohort of women with varying a priori risk due to obstetrical history.…”
Section: Commentmentioning
confidence: 99%
“…In conclusion, in patients without a poor obstetrical history prior to the diagnosis of unicornuate uteri, rates of midtrimester pregnancy loss and spontaneous preterm birth were lower than previously described. 6,14,[22][23][24][25][26]28 When a unicornuate uterus is incidentally detected, women could probably be reassured that the risk of adverse pregnancy outcomes beyond the first-trimester is lower than studies that include ascertainment bias would indicate. However, the rates of placental abnormalities are significantly higher, often necessitating preterm delivery.…”
Section: Commentmentioning
confidence: 99%
“…Uterine malformations are the most common defects of the female reproductive system, occurring with the incidence of about 4% in the general population of women [1]. It is reported that uterine septum, an important type of uterus defects, occurred with the incidence of 24% and constituted a risk of infertility, miscarriage and complications of pregnancy as well as childbirth [2,3]. Abortion rate in patients with uterine septum is as high as 77.4% with only 6-28% of the live birth rate [4,5].…”
Section: Introductionmentioning
confidence: 99%